Improvement of the Degradation of Tensile and Impact Strength of Water-aged Sisal Fiber-reinforced Polyester Composites: A Comparative Study on the Effects of Hybridizations, Hybrid Layering Sequences, and Chemical Treatments - Abrha Gebregergs Tesfay; Mulu Bayray Kahsay; P.S. Senthil Kumar (Journal of Natural Fibers, 2022)
This research aims to reduce the degradation of sisal fiber-reinforced polyester composites due to water absorption through chemical treatments and hybridizations. Sisal fibers were treated using sodium hydroxide (NaOH) and baking soda (NaHCO3). Unidirectional glass and carbon fibers were chosen as hybrid fibers. Thirteen laminates of pure sisal fibers, hybridized with glass or carbon fibers at different stacking sequences and volume fractions, were prepared using the hand layup technique. The laminates were examined for tensile and impact strength at dry and wet conditions. The effects of baking soda and sodium hydroxide treatments, glass and carbon fibers hybridization, and the sequence and volume of the hybrid fibers on the tensile strength, impact strength, water absorption, and degradation of the laminates were studied and compared. Chemical treatments and hybridizations have enhanced the tensile and impact strength of the composites. Significant reduction in the water uptake rate and degradation of the laminates were observed. Almost 166% and 87%, respectively, improvements were obtained in the tensile and impact strength of the dry samples. Moreover, more than 74% reduction in water uptake, and 84.7% and 91.7%, respectively, improvements in the degradation of the tensile and impact strengths were discovered.